Brazing of alumina ceramic and graphite to titanium by amorphous foil Ti-20Zr–20Cu–20Ni. As the filler metal - Shapiro, A.E. (Адгезия расплавов и пайка материалов, 2015)
Brazed joints of alumina ceramic and graphite with titanium were tested for shear strength. This was followed by investigation of their microstructure and phase compositions using scanning electron microscopy and EDS analysis. Active diffusion of alloy and ceramic components during brazing resulted in the formation of sophisticated microstructures characterized by a non-uniform distribution of elements. No intermetallic layers were found at the titanium interface, both in graphite-titanium and ceramic-titanium brazed joints. This new effect, and post-braze diffusion heat treatment, may improve the strength and ductility of brazed joints of dissimilar base materials.